Influences of naringin supplementation on ruminal fermentation, inflammatory response, antioxidant capacity and bacterial community in high-concentrate diet of fattening goats - Hua Sun; Fangfang Zhao; Fuyin Hou; Yaqian Jin; Xinzhao Zhang; Yi Ma; Ying Zhang; Yaotin Fan; Zhiqing Yang; Hongrong Wang (Italian Journal of Animal Science, 2022)
The objective of this study was to evaluate the effects of dietary naringin supplementation on rumen fermentation, inflammatory response and bacterial communities in fattening goats fed high-concentrate diet. Twenty four Boer male goats were randomly divided into three groups and assigned to receive dietary treatments. The three dietary treatments were a normal diet, a high-concentrate diet and a high-concentrate diet supplemented with 500 mg of naringin/kg of dry matter intake. Rumen fluid and plasma samples were collected at the end of the animal trial. Rumen fluid were analysed for pH, short-chain fatty acids, endotoxin (lipopolysaccharide, LPS) and microbiota. Illumina Miseq sequencing of the 16S rRNA gene was applied to investigate ruminal bacterial communities. The concentrations of interleukin −6 and tumour necrosis factor alpha as well as LPS-binding protein, haptoglobin, serum amyloid A and the activities of antioxdant enzymes in plasma were analysed. The result showed that feeding the high concentrate diet shifted the ruminal fermentation pattern from acetate towards propionate and valerate, and improved growth performance compared with the control group. However, the high concentrate diet promoted ruminal pH reduction and LPS release, modified bacterial communities and increased systemic inflammatory response. Naringin supplementation increased molar proportions butyrate and decreased valerate. Naringin supplementation decreased inflammatory response and increased the activities of antioxdant enzymes in plasma. Moreover, naringin addition increased the relative abundance of Bacteroidetes at the phylum level and Rikenellaceae_RC9_gut_group at the genus level. Taken together, these results suggest that dietary supplementation with naringin attenuates high grain diet-induced inflammatory response and modifies ruminal fermentation. HIGHLIGHTS Dietary supplementation of naringin decreased inflammatory response and increased the activities of antioxdant enzymes in fattening goats. Naringin supplementation changed ruminal microbiota of fattening goats. Naringin has potential for use as feed additive to modify ruminal fermentation in a high-grain intensive ruminant production.